RECIPROCAL TEACHING AS AN INSTRUCTIONAL TECHNIQUE IN TEACHING READING COMPREHENSION OF FACTUAL REPORT TEXT TO THE ELEVENTH GRADERS (RETAIN, 2016)
RECIPROCAL TEACHING AS AN INSTRUCTIONAL TECHNIQUE IN TEACHING READING COMPREHENSION OF FACTUAL REPORT TEXT TO THE ELEVENTH GRADERS Astutik Dyah Handayani English Education Department, Language and Art Faculty, Surabaya State University. astutikh@mhs.unesa.ac.id Dr. Oikurema Purwati, M.A., M.Appl. English Education Department, Language and Art Faculty, Surabaya State University. pungki_unesa@yahoo.co.id Abstrak Penelitian ini bertujuan untuk mendeskripsikan kontribusi dari penerapan pembelajaran teknik Reciprocal Teaching terhadap pemahaman membaca siswa pada teks faktual ilmiah untuk kelas sebelas, untuk mendeskripsikan hasil pekerjaan siswa terhadap pemahaman membaca pada teks faktual ilmiah setelah diterapakan teknik Reciprocal Teaching dalam pembelajaran pemahaman membaca kelas sebelas, dan untuk mendeskripsikan respon siswa terhadap penerapan Reciprocal Teaching sebagai teknik pembelajaran untuk keterampilan pemahaman membaca siswa. Penelitian ini didesain sebagai penelitian kualitatif. Hasil dari penelitian ini menunjukkan bahwa penerapan Reciprocal Teaching memberikan kontribusi yang bermanfaat bagi keterampilan membaca siswa dan menunjukkan respon yang baik pada siswa. Reciprocal Teaching membantu siswa untuk lebih mandiri dalam pembelajaran membaca dengan bantuan yang sedikit dari guru. Sebagai tambahan, siswa dapat saling berbagi pengetahuan dan pemahaman dengan siswa yang lain. Kata Kunci: Reciprocal Teaching, Pemahaman membaca, Teks Faktual Ilmiah. Abstract This study was conducted to describe the contribution from the implementation of Reciprocal Teaching technique in teaching reading comprehension of factual report text to the eleventh graders, to describes the students’ result in reading comprehension of factual report text after the implementation of Reciprocal Teaching for teaching reading comprehension to the eleventh graders, and to describe the students’ response towards the the implementation of Reciprocal Teaching as an instructional technique of their reading comprehension skill. This research was designed as a qualitative research. The results of the study showed that the implementation of Reciprocal Teaching gave useful contribution to the students’ reading comprehension and showed good response towards students. Reciprocal Teaching helps students to be more independent in their reading, with minimum help from the teacher. In addition, they could share their knowledge and comprehension with other students. Keywords: Reciprocal Teaching, Reading Comprehension, Factual Report Text.